E-Learning in Modern Education: Journey, Implementation, Challenges, and Future Potential - Didik Himmawan; Rena Mayang Seruni (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
E-learning has revolutionized the world of education by offering greater flexibility and accessibility through the use of technology. This method allows students to learn independently anytime and anywhere, integrating a variety of engaging learning media. However, its implementation faces challenges, including uneven internet access and the need for high levels of self-discipline from students. However, with technological advances such as AI, VR, and AR, e-learning has great potential to become more personalized, immersive, and adaptive. The implementation of e-learning in educational institutions such as schools and universities shows similarities in the use of technology and material management, but differs in the level of independence required by students and the context in which it is used. This research highlights that e-learning has advantages such as flexibility in time, broad access to materials, and personalization, but also disadvantages such as limited social interaction and infrastructure issues. Overall, e-learning continues to transform into an inclusive and effective educational solution, opening up new opportunities for lifelong learning.